PRODUCTIVE WAQF MODEL FOR WOMEN FISHERS’ EMPOWERMENT: INSIGHTS FROM COMMUNITY-BASED DEVELOPMENT AND MAQASHID SHARIA - Putri Purwandari Hasan; Nurul Fitrah Islamiah; Asmirawati (Universitas Airlangga, 2026)
Women fishers play an important role in supporting the coastal economy. However, the productivity of women fishers is still relatively low due to limited business capital, production facilities, and sustainable institutional support. Productive waqf as an Islamic financial instrument is considered strategic because it can provide access to interest-free capital, is in line with maqashid sharia and blue economy principles, and ensures sustainable benefits for women fishers. Therefore, this study aims to design a productive waqf model for women fishers' empowerment by integrating the concepts of community-based development and maqashid sharia principles. The research was conducted using a qualitative approach and case study method in a community of women fishers in a coastal area in South Sulawesi. Data were collected through semi-structured interviews and focus group discussions with groups of women fishers and sharia cooperative managers in the area. The results of data collection were then analyzed thematically using Nvivo 15 software. The results of the study show that there are major obstacles that limit the productivity of women fishers, namely limited capital, limited means of production, and low bargaining power. Institutional support through sharia cooperatives plays an important role in the distribution of business capital, the provision of means of production, increasing production capacity, and strengthening community solidarity. The output of this study is a conceptual model of community-based productive waqf that contributes to the development of Islamic economics and blue economy literature in Indonesia The research was conducted using a qualitative approach and case study method in a community of women fishers in a coastal area in South Sulawesi. Data were collected through semi-structured interviews and focus group discussions with groups of women fishers and sharia cooperative managers in the area. The results of data collection were then analyzed thematically using Nvivo 15 software. The results of the study show that there are major obstacles that limit the productivity of women fishers, namely limited capital, limited means of production, and low bargaining power. Institutional support through sharia cooperatives plays an important role in the distribution of business capital, the provision of means of production, increasing production capacity, and strengthening community solidarity. The output of this study is a conceptual model of community-based productive waqf that contributes to the development of Islamic economics and blue economy literature in Indonesia.